The global relevance of locally grounded ethnobiology - Álvaro Fernández-Llamazares; Irene Teixidor-Toneu; Chelsey Geralda Armstrong; Julián Caviedes; José Tomás Ibarra; Dana Lepofsky; Alex C. McAlvay; Zsolt Molnár; R. Mónica Moraes; Guillaume Odonne; Melissa R. Poe; Abolfazl Sharifian Bahraman; et al. (BMC, 2024)
Abstract While ethnobiology is a discipline that focuses on the local, it has an outstanding, but not yet fully realized potential to address global issues. Part of this unrealized potential is that universalistic approaches often do not fully recognize culturally grounded perspectives and there are multiple challenges with scaling up place-based research. However, scalability is paramount to ensure that the intimate and context-specific diversity of human-environmental relationships and understandings are recognized in global-scale planning and policy development. Here, we identify four pathways to enable the scalability of place-based ethnobiological research from the ground up: local-to-global dialogues, aggregation of published data, multi-sited studies, and geospatial analyses. We also discuss some major challenges and consideration to encourage continuous reflexivity in these endeavours and to ensure that scalability does not contribute to unnecessarily decontextualizing, co-opting, or overwriting the epistemologies of Indigenous Peoples and local communities. As ethnobiology navigates multiple scales of time and space and seeks to increase its breadth, this study shows that the use of deliberately global approaches, when carefully nested within rich field-based and ecological and ethnographically grounded data, can contribute to: (1) upscaling case-specific insights to unveil global patterns and dynamics in the biocultural contexts of Indigenous Peoples and local communities; (2) bringing ethnobiological knowledge into resolutions that can influence global environmental research and policy agendas; and (3) enriching ethnobiology's field-based ethos with a deliberate global analytical focus.